2016
DOI: 10.1111/pde.12746
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intralesional Triamcinolone in the Treatment of Keloids in Children

Abstract: Triamcinolone acetonide is highly effective for the treatment of pediatric keloids. There is no relationship between clinical response and the factors evaluated, such as lesion location, etiology and age of the keloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…A number of other studies support a multimodal approach . Acosta and colleagues found that intralesional triamcinolone acetonide was highly effective as a single‐modality treatment for pediatric keloids . Newer treatment modalities such as pulsed dye laser, fractional ablative lasers and 5‐fluorouracil with or without topical steroids have shown promising results in keloid management .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of other studies support a multimodal approach . Acosta and colleagues found that intralesional triamcinolone acetonide was highly effective as a single‐modality treatment for pediatric keloids . Newer treatment modalities such as pulsed dye laser, fractional ablative lasers and 5‐fluorouracil with or without topical steroids have shown promising results in keloid management .…”
Section: Discussionmentioning
confidence: 99%
“…The only significant variable associated with recurrence in our study was the size of the keloid. In some studies, keloids on the trunk and extremities and those undergoing multimodal treatment have been associated with recurrence, whereas others have found no relationship between treatment outcome and keloid location, duration of the keloid, or etiology …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective clinical trial in 21 children also showed that monthly intralesional TAC infiltration (20 mg/cm 3 , ≤40 mg/session) for 3 months decreased the average size of the 25 keloids by 82.7%. Only one keloid did not respond to treatment, even after five infiltrations . The side effects of intralesional steroid administration are mainly pain, hypopigmentation, hyperpigmentation, skin atrophy, and telangiectasia…”
Section: Current and Emerging Pharmaceuticals In Clinical Keloid Manamentioning
confidence: 95%
“…Only one keloid did not respond to treatment, even after five infiltrations. 43 The side effects of intralesional steroid administration are mainly pain, hypopigmentation, hyperpigmentation, skin atrophy, and telangiectasia. 41 The therapeutic effects of BTA are conflicting and not convincing.…”
Section: Pharmaceutical Therapies Targeting the Prolonged Inflammatmentioning
confidence: 99%